Impact of organisational climate on employee well-being and healthy relationships at work: A case of social service centres - Andrius Janiukštis; Kristina Kovaite; Tomas Butvilas; Paulius Šumakaris (Administrative Sciences, 2024)
Multiple studies highlight the crucial role of management of a positive organisational climate, which in turn contributes to employee well-being and healthy workplace relationships and mitigates the occurrence of negative behaviour, including harassment at the workplace. Furthermore, contemporary scholars emphasise the importance of open and transparent communication channels in reducing workplace tensions and improving employee mental health. However, the interrelationship between organisational climate, open communication, employee well-being, and negative behaviours in the workplace is a complex phenomenon. Despite the relevance and interest in organisational climate on employee well-being, limited efforts have been devoted to the area of relationships and causality, and straightforward answers about the objective links between these phenomena and their general nature remain complex. Therefore, this study aims to strengthen the understanding of the impact of the organisational climate on employee well-being and negative behaviours in the workplace. This is the first study that applied causality to the investigated problem to identify statistical relationships between the variables. This study was conducted in Lithuanian social service centres and schools, focussing on professionals with a high psychological risk at work due to their nature. This study offers valuable contributions and provides a comprehensive and profound insight into the management field, focussing on the impact of the organisational climate. The values of harassment in the workplace are explained by the values of organisational climate and employee well being. This study demonstrates that improving the organisational climate contributes to employee well-being and healthy relationships and reduces the prevalence of negative behaviours in the workplace. This study introduces the academic and practical implications and suggests the pathways for further research.
Keywords: 350; organisational climate; employee well-being; negative behaviour and harassment at theworkplace; discourse; communication as connecting means